5 un 6 gadīgu bērnu sensoro spēju sekmēšana spēlēs - Cera, Evita (Latvijas Universitāte, 2011)
Darba nosaukums: 5 un 6 gadīgu bērnu sensoro spēju sekmēšana spēlēs. Darba mērķis: izzināt pirmsskolas vecuma bērnu sensoro spēju pieredzi un tās sekmēšanas iespējas spēlēs. Darba pirmajā daļā autore analizē bērnu sensoro spēju attīstības likumsakarības, to nozīmi bērnu attīstībā kopveselumā. Otrajā daļā tiek apskatītas spēles atšķirības, to funkcijas psihologu un pedagogu skatījumā, kā tās sekmē bērnu attīstību un sensoro spēju pieredzi, izvirzot nosacījumus bērna attīstības veicināšanai. Trešajā daļā autore veic praktisko izpēti, kā ar spēļu palīdzību var izzināt vecākā pirmsskolas vecuma bērnu sensoro spēju pieredzi. Pētījums veikts Bauskas novada X pirmsskolā, sešgadīgo bērnu grupā. Pētījumā piedalījās 10 bērni, 10 pedagogi. Pētījuma gaitā apstiprinājās izvirzītā hipotēze, ka spēles sekmē bērnu sensoro spēju attīstību. Darba saturs: darba apjoms 92 lpp., 26 attēli, 3 tabulas, 29 pielikumi. Atslēgvārdi: sensorais, intelekts, spēle.

The topic of the paper: Promotion of the sensory abilities of 5 and 6 year-old children through games. The aim of the paper: to study the pre-school age children’s experience of sensory abilities and opportunities of promoting them through games. In Part 1 the author analyses regularities of the development of children’s sensory abilities, their significance in children’s development as a whole. Part 2 examines differences of games, their functions viewed by psychologists and teachers, how they promote children’s development and experience of sensory abilities, by setting conditions for encouraging child’s development. In Part 3 the author carries out practical investigation, how to explore senior pre-school age children’s experience of sensory abilities with the help of games. The study has been carried out in a group of six-year-old children of Nursery school X, Bauska region. 10 children and 10 teachers took part in the present study. In the course of the study the propounded hypothesis, that games promote the development of children’s sensory abilities, proved true. The contents of the paper: the amount of the paper 92 pages, 26 pictures, 3 tables, 29 appendixes. The keywords: sensory, intellect, game.
Promotion of the sensory abilities of 5 and 6 year-old children through games
Keywords: Pedagoģija